THE EFFECT OF ASSMBLR EDU APPLICATION USE ON HIGH SCHOOL STUDENTS' INTERESTS AND LEARNING OUTCOMES IN HYDROCARBONS - Faros Nabawi Siregar; Saronom Silaban (Journal Analytica Islamica, 2026)
This study aims to analyze the effect of using the Augmented Reality (AR)-based Assemblr Edu application on high school students' learning interest and cognitive learning outcomes in hydrocarbon material. The study used a quasi-experimental approach with a nonequivalent control group design, involving two classes selected through cluster random sampling techniques, namely the experimental class using Assemblr Edu and the control class with conventional learning. The research instruments included a multiple-choice learning outcome test and a Likert-scale learning interest questionnaire. Data analysis was carried out through normality tests, homogeneity tests, and independent t-tests. The results showed a significant difference between student learning outcomes in the experimental and control classes (Sig. 2-tailed = 0.000 < 0.05), which indicates that the use of Assemblr Edu has a positive effect on improving student learning outcomes. In addition, student learning interest in the experimental class was in the very high category with an average score of 3.56. These findings indicate that three-dimensional and interactive visualization of chemical concepts through AR can increase students' affective engagement and cognitive understanding. Thus, Assemblr Edu has the potential to be an effective, innovative learning medium for abstract chemistry material.